(untitled) (Psychology Travelogs, 2024)
The article addresses the problem of professional self-realization, focusing on it as a complex psychological and social phenomenon. Self-realization is considered a continuous process of personal growth, deeply connected to self-awareness, social interaction, and professional achievement. It integrates a person’s internal world with external experience, guiding them toward self-expression in both personal and professional life. The article discusses key aspects of self-realization, such as goal-setting, value selection, and creativity, which are essential for personal development and success. Drawing on the works of renowned scholars like A. Bandura, A. Maslow, C. Rogers, and others, the author highlights various approaches to understanding self-realization, noting the significant influence of social and psychological factors. Ukrainian researchers have also contributed to the study of self-realization in the professional context, investigating its impact on individual growth and competency development. The article explores the importance of self-determination, self-regulation, and professional self-actualization as key components of a person’s ability to shape their own life. It also emphasizes that self-realization is not static but an ongoing process requiring constant effort, self-reflection, and adaptation to new challenges. The conclusion stresses the necessity of further research to deepen our understanding of how individuals can achieve full self-actualization, particularly in professional settings, while balancing personal growth with societal expectations. This research is crucial for fostering personal development and enhancing one’s ability to contribute meaningfully to society.